1994
DOI: 10.1182/blood.v84.2.490.bloodjournal842490
|View full text |Cite
|
Sign up to set email alerts
|

Solvent/detergent-treated plasma suppresses shear-induced platelet aggregation and prevents episodes of thrombotic thrombocytopenic purpura

Abstract: Two children with congenital chronic relapsing thrombotic thrombocytopenic purpura (TTP) have episodes every 3 weeks. These relapses can be prevented by the infusion of normal fresh-frozen plasma (FFP) without concurrent plasmapheresis. We conducted a study to determine whether the exposure of normal plasma to agents that inactivate human immunodeficiency virus and other viruses destroys the component necessary for the effective treatment of this type of TTP that requires only plasma infusion to prevent or rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 15 publications
4
57
0
Order By: Relevance
“…In this study, SDFFP had normal VWF antigen but reduced VWF activity. Moake et al (1994) have previously shown that SDFFP lacks the high molecular weight multimeric forms of VWF:Ag. We have confirmed this observation and, in addition have demonstrated that the VWF:Ag multimeric distribution in SD cryoprecipitate is also abnormal, reflecting that in whole plasma.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, SDFFP had normal VWF antigen but reduced VWF activity. Moake et al (1994) have previously shown that SDFFP lacks the high molecular weight multimeric forms of VWF:Ag. We have confirmed this observation and, in addition have demonstrated that the VWF:Ag multimeric distribution in SD cryoprecipitate is also abnormal, reflecting that in whole plasma.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports of successful plasma exchange with S/D plasma in TTP have focused on the chronic relapsing form of the disease, usually in childhood (Moake et al, 1994). In this case, the patient failed to enter sustained clinical remission despite standard therapy and was therefore classified as having unremitting TTP, and a spontaneous remission was therefore unlikely.…”
Section: Patient and Methodsmentioning
confidence: 90%
“…Thus cryosupernatant, deficient in higher molecular weight forms of VWF, may benefit patients refractory to standard FFP. S/Dtreated plasma, for unknown reasons, lacks high molecular weight forms of VWF (Moake et al, 1994), and may be beneficial primary plasma replacement in TTP.…”
mentioning
confidence: 99%
“…[42][43][44] The rationale for its specific use is that, for unknown reasons, the highest-molecularweight multimers of vWF are lost in the production process, similar to the reduction seen when CRP was analyzed. 42 One study demonstrated that S/D plasma suppressed shear-induced platelet aggregation in vitro and was effective in preventing disease recurrence in two children with chronic relapsing TTP (via infusion). 42 Like FFP and CRP infusions in chronic relapsing TTP, S/D plasma was associated with the rapid disappearance of unusually large vWF multimers.…”
Section: Crp In the Treatment Of Ttpmentioning
confidence: 99%
“…42 One study demonstrated that S/D plasma suppressed shear-induced platelet aggregation in vitro and was effective in preventing disease recurrence in two children with chronic relapsing TTP (via infusion). 42 Like FFP and CRP infusions in chronic relapsing TTP, S/D plasma was associated with the rapid disappearance of unusually large vWF multimers. Another case report described a patient with refractory TTP who achieved a sustained remission upon the use of S/D plasma as an exchange medium.…”
Section: Crp In the Treatment Of Ttpmentioning
confidence: 99%